2019
DOI: 10.1038/s41467-019-12460-7
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Cu1 species over nanodiamond-graphene for semi-hydrogenation of acetylene

Abstract: The design of cheap, non-toxic, and earth-abundant transition metal catalysts for selective hydrogenation of alkynes remains a challenge in both industry and academia. Here, we report a new atomically dispersed copper (Cu) catalyst supported on a defective nanodiamond-graphene (ND@G), which exhibits excellent catalytic performance for the selective conversion of acetylene to ethylene, i.e., with high conversion (95%), high selectivity (98%), and good stability (for more than 60 h). The unique structural featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
216
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(232 citation statements)
references
References 41 publications
(29 reference statements)
12
216
2
2
Order By: Relevance
“…[ 226‐228 ] Tremendous efforts have been devoted to developing the methods of precise synthesis and to understanding the structure‐activity relations in a number of catalytic reactions. [ 226‐233 ] A thorough study of the particle size effect as well as taking the counterparts of ultrafine clusters and single atoms into account is highly necessary, which could provide a much deeper insight of structure‐activity relations and facilitate rational design of advanced metal catalysts. However, such studies in the real catalyst systems have been rarely reported.…”
Section: Particle Size Effect In Metal Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[ 226‐228 ] Tremendous efforts have been devoted to developing the methods of precise synthesis and to understanding the structure‐activity relations in a number of catalytic reactions. [ 226‐233 ] A thorough study of the particle size effect as well as taking the counterparts of ultrafine clusters and single atoms into account is highly necessary, which could provide a much deeper insight of structure‐activity relations and facilitate rational design of advanced metal catalysts. However, such studies in the real catalyst systems have been rarely reported.…”
Section: Particle Size Effect In Metal Catalysismentioning
confidence: 99%
“…Such impressive capability of coking inhibition is attributed to spatial confinement of single sites, which was also observed on other SACs. [ 233,237 ]…”
Section: Particle Size Effect In Metal Catalysismentioning
confidence: 99%
“…[33][34][35] With the blooming development of SACs, the intrinsic defects have regarded as potential anchoring sites for stabilizing the metal species. [18,[36][37][38][39] Zhang and coworkers employed a pulsed laser deposition (PLD) technique to dig the desired vacancies with different sizes in the graphene matrix, and followed by metal dopant deposition. [36] To be investigated by aberration-corrected high-resolution transmission electron microscope (HRTEM), it shows that bi-vacancy or larger vacancies are the ideal trapping site for transition metal atoms, which have much larger atomic radii than carbon (Figure 2a,b).…”
Section: Defects Engineeringmentioning
confidence: 99%
“…[18] Besides, the defects of carbon supports are also critical for manipulating the electronic structure of SACs to increase the chemoselectivity relative to their bulk counterparts. [38,[40][41][42] For example, Ma and co-workers found that the catalyst with single Pd atoms on a defective nanodiamond-graphene support (Pd 1 / ND@G) shows an excellent performance for selective hydrogenation of acetylene to ethylene, in which the yield of ethylene is more than 90% under the 100% conversion efficiency of acetylene, and overwhelms that of Pd nanoclusters (Figure 2h). [41] The combination of XAFS and DFT analyses disclose that the atomic Pd is formed a pyramidal structure through bonding with three carbon atoms, which energetically favors desorption of the C 2 H 4 intermediate to suppress the further hydrogenation of the targeted product.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The alkyne semihydrogenation activity of single-atom Au was dependent on the substrates: structure insensitive for alkynols with γ-OH and unfunctionalized alkynes, while sensitive for alkynols with α-OH [47]. More recently, Ma and co-workers [48] reported that non-noble metal SACs Cu supported on nanodiamond-graphene exhibited 95% acetylene conversion and 98% ethylene selectivity.…”
Section: Introductionmentioning
confidence: 99%